2011
DOI: 10.1177/0884533610392920
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil‐Based Fat Emulsion Versus Soy Oil‐Based Fat Emulsion in Abdominal Oncologic Surgery

Abstract: In parenteral nutrition (PN), essential fatty acids are provided by soy oil-based fat emulsions, which may exert adverse effects on the immune system and lipid peroxidation. Olive oil -based fat emulsions have been said to prevent these undesired effects. This study compares effects of olive oil - and soy oil -based fat emulsions in 22 patients who underwent abdominal surgery for cancer. The first group (n = 10) received soy oil -based fat emulsion; the second group (n = 10) received olive oil -based fat emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In fact, due to importance of the environment, culture condition, and soil to the final composition of the oil, difference exists between inter/intraregion EVOO compounds. On the other context, due to the benefic effect of the oil, we can propose the EVOO as an adjuvant, vehicle, or emulsion in a treatment context and have a synergistic effect [40] or to prevent undesired effects of other used lipids [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, due to importance of the environment, culture condition, and soil to the final composition of the oil, difference exists between inter/intraregion EVOO compounds. On the other context, due to the benefic effect of the oil, we can propose the EVOO as an adjuvant, vehicle, or emulsion in a treatment context and have a synergistic effect [40] or to prevent undesired effects of other used lipids [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In the olive oil group, infection types included respiratory ( n = 3), abdominal ( n = 3), urinary tract ( n = 4), and surgical incision ( n = 1), while in the olive + fish oil group, infections included abdominal ( n = 1), surgical wound ( n = 1), and blood stream infection ( n = 1) [ 33 ]. In several studies, no significant difference between olive oil and soybean oil groups in infection rates was noted; however, these studies were likely underpowered to detect significant differences [ 26 , 38 , 39 , 40 ]. In the largest study to date, Jia and colleagues reported that olive oil-based ILE was associated with a significantly lower infection rate compared with soybean oil-based ILE ( Figure 4 ) [ 20 ].…”
Section: Immune Functionmentioning
confidence: 99%
“…In contrast, numerous clinical studies have investigated markers of oxidative stress including total antioxidant status (TAS), total antioxidant capacity, TBARS, F2-isoprostane, vitamin Eα-tocopherol levels, pentane, or malondialdehyde (MDA). Most studies have reported no differences in oxidative stress markers between olive oil-based and soybean oil-based [ 20 , 38 , 40 , 43 , 59 , 60 , 61 ], MCT/LCT [ 60 , 62 , 63 ], or fish oil-based [ 64 , 65 ] ILE ( Table 3 ). Furthermore, a systematic review of studies in hospitalized pediatric patients suggested that available studies do not support one ILE over another with regard to benefits on oxidative stress [ 66 ].…”
Section: Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in a randomized controlled study with surgical adult patients (which differed by the PN delivery system (3-chamber system vs. lipids separate) and electrolyte dosing (standard dosing vs. custom prescription) as well as differing in IVLE) [ 25 ], patients receiving olive oil based IVLE experienced significantly fewer overall infections and higher albumin and pre-albumin compared with patients receiving Intralipid. In a separate non-randomized trial, no differences in catheter infections were observed along with ALT and TB between patients matched on age and gender after seven days of PN with either soybean or olive oil based IVLE post abdominal surgery, however ALP was significantly higher in the olive oil-based emulsion group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%